Recuperação sustentável de lítio a partir de baterias de íon de lítio: um estudo comparativo de técnicas pirônicas e hidrometalúrgicas: Sustainable lithium recovery from lithium-ion batteries: a comparative study of pyro and hydrometallurgical techniques - de Oliveira, Andriela Dutra Norberto; da Cunha, Armando Lucas Cherem; Sobral, Luis Gonzaga Santos; Junior, Isaías Vieira (RCMOS - Revista Científica Multidisciplinar O Saber, 2024)
Different types of Batteries are used in many diverse applications, such as cars, radios, laptops, mobile phones, and watches. They are classified as primary and secondary batteries. The former is known as an alkaline battery, made from zinc and manganese as its primary components. It is mainly used for household purposes, converting chemical energy directly into electrical energy. The latter is usually made of nickel (Ni), cadmium, nickel metal hydride, or lithium-ion, and is mainly used in mobile phones, electronic devices, cameras, etc. The primary concern with batteries is their environmental impact at the end of their useful life. Among all types of batteries, Lithium-ion batteries (LIBs) are gaining worldwide interest owing to their use in almost all modern life devices. In addition, it is of paramount importance to develop new technologies to minimize environmental impact during the disposal of such heavy-metal-bearing residues, since, on the one hand, the metals they contain can affect the environment and, on the other hand, these metals are valuable at an industrial level. In this work, the recoveries of lithium and manganese from the cathodes of exhausted lithium-ion batteries will be investigated using a pyrometallurgical chlorination process, followed by a hydrometallurgical process for the proper solubilisation of the lithium, manganese, and cobalt chlorides formed. The tests were carried out in isothermal conditions in an alumina reactor, so that it could be operated in corrosive atmospheres. The effect of temperature and reaction time on lithium, manganese, and cobalt extractions was also considered. The reagents, products, and solid residues of chlorination were characterized by atomic absorption spectrometry (AAS) and X-ray diffraction (XRD). The experimental results will be analysed to assess the efficiency of lithium, manganese, and cobalt extractions as LiCl, MnCl2, and CoCl2, respectively. Once these metals were solubilized, lithium was precipitated as carbonate, the raw material for subsequent battery production.